Utopías urbanas : geopolíticas del deseo en América Latina - Heffes, Gisela, 1971- (Colección Nexos y diferencias, 2013)
It explores the relationship between the emergence of the American city as a geopolitical reality and the construction of the utopian ideal in several Latin American writings, considering the diversity inherent in the utopian fictional ideas, ideological and intellectual, and a perfect setting and idealized society.